Efeitos da respiração em freno-labial sobre os volumes pulmonares e o padrão de hiperinsuflação dinâmica em pacientes com asma - Pinto, Janaína Maria Dantas (2011)
Objectives: To evaluate how to develop dynamic hyperinflation (DH) during exercise, the influence of pursed-lip breathing in (PLB) on breathing pattern and operating volume in patients with asthma. Methods: We studied 12 asthmatic patients in three moments: (1) anthropometry and spirometry, (2) submaximal incremental cycle ergometer test in spontaneous breathing and (3), submaximal incremental test on a cycle ergometer with PLB using the Opto-electronic plethysmography. Results: Evaluating the end-expiratory lung volume (EEV) during submaximal incremental test in spontaneous breathing, patients were divided into euvolume and hyperinflated. The RFL has increased significantly, the variation of the EEV group euvolume (1.4L) and decreased in group hyperinflated (0.272L). In group volume observed a significant increase of 140% in Vt at baseline, before exercise, comparing the RFL and spontaneous breathing. Hyperinflated group was observed that the RFL induced significant increases of Vt at all times of the test incremental baseline, 50%, 100% load and 66% recovery, 250%, 61.5% and 66% respectively. Respiratory rate decreased significantly with PLB at all times of the submaximal incremental test in the group euvolume. The speed of shortening of inspiratory muscles (VtRcp/Ti) in the hyperinflated increased from 1.6 ± 0.8L/s vs. 2.55 ± 0.9L/s, whereas in the RFL euvolume group ranged from 0.72 ± 0.31L/s vs. 0.65 ± 0.2L/s. The velocity of shortening of the expiratory muscles (VtAb/Te) showed similarity in response to RFL. In group hyperinflated varied vs. 0.89 ± 0.47 vs. 0.80 ± 0.36 and ± 1.17 ± 1L vs. 0.78 ± 0.6 for group euvolume. Conclusion: Different behavior in relation to EEV in patients with moderate asthma were observed, the HD and decreased EEV in response to exercise. The breathing pattern was modulated by both RFL performance as at home, making it more efficient